MO821OXYGEN EXTRACTION RATIO AND MORTALITY RISK IN HAEMODIALYSIS PATIENT: A MULTICENTRE STUDY. (29th May 2021) - Rotondi, Silverio; Tartaglione, Lida; Muci, Maria Luisa; Panocchia, Nicola; Gesuete, Antonio; Papalia, Teresa; Solmi, Luigi; Mazzaferro, Sandro
Abstract: Background and Aims: Patients on haemodialysis (HD) suffer a very high rate of cardiovascular mortality with some evidence suggesting a possible association with decreasing blood oxygen saturation (SO2) during sessions. The ratio between arterial SO2 (SaO2) and central venous SO2 (ScvO2) or Oxygen Extraction Ratio (OER), which represents an estimate of the amount of oxygen claimed by peripheral tissues and of the haemodialysis related hypoxic stress, might represent a new prognostic factor. Method: We evaluate the relationship between OER values and mortality risks in HD patients in a prospective multicentre observational study. We enrolled chronic HD patients with permanent central venous catheter (CVC) and no fistula, in whom ScvO2 measurement is at hand and SaO2 is available with a peripheral oxymeter. OER ([(SaO2−ScvO2)/SaO2]×100) was measured before and after HD at enrolment (HD OER sessions) in each patients, and a one-year follow-up was planned to record the number of deaths. Results: In 101 patients (age 71.5 ± 14 years on dialysis for 47 ± 38 months), during 9 ± 6 months of follow up, we recorded 35 deaths. Patients were then divided into two groups, above or below the median value of pre-HD OER, which was 30%. In these groups, the average incidence of deaths was 12% (24 deaths) and 5, 5% (11 deaths) respectively (p<0.05), with significantly different survival curves (Kaplan-Meier log rank test = 0.04, fig ). No difference in mortality was evident if we divided patients according to the median intradialytic change in OER value. Conclusion: Patients with pre-HD OER > 30% have a higher mortality risk, most probably secondary to reduced capability to respond to HD related oxygen requirements. OER is novel biomarker to identify patients at greatest clinical risk.